2020
DOI: 10.1051/0004-6361/202038186
|View full text |Cite
|
Sign up to set email alerts
|

Tracing bulk elemental ratios in exoplanetary atmospheres with TiO chemistry

Abstract: Deciphering the bulk elemental abundances of exoplanetary atmospheres is not an easy task, yet it is crucial to understanding the formation history of planets. The purpose of this work is to show that the observability of TiO features at optical wavelengths in the transmission spectra of hot Jupiter atmospheres is sensitive to the bulk chemical properties of the atmosphere. To this end, we ran a grid of chemical models, which include TiO formation and destruction, for the ultra-hot Jupiter WASP-19b and an ultr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…For nitrogen we use N 2 and NH 3 , where most of the nitrogen should be in the form of N 2 (e.g., Bosman et al 2019). Even though Ti, Al, K, Na, and V are not very abundant and thus do not contribute significantly to the planetary accretion rates, we include these elements in our model because they can be observed in the atmospheres of hot Jupiters and could also play a crucial role for the chemical evolution inside the atmospheres (Ramírez et al 2020).…”
Section: Compositionsmentioning
confidence: 99%
“…For nitrogen we use N 2 and NH 3 , where most of the nitrogen should be in the form of N 2 (e.g., Bosman et al 2019). Even though Ti, Al, K, Na, and V are not very abundant and thus do not contribute significantly to the planetary accretion rates, we include these elements in our model because they can be observed in the atmospheres of hot Jupiters and could also play a crucial role for the chemical evolution inside the atmospheres (Ramírez et al 2020).…”
Section: Compositionsmentioning
confidence: 99%
“…It is not included in the UMIST Database for Astrochemistry (UDfA) (McElroy et al 2013) or in Kinetic Database for Astrochemistry (KIDA) (Wakelam et al 2012). We incorporate available reactions (Tsai et al 2021;Churchwell et al 1980;Ramírez et al 2020), but these are small in number. We adopted Si-based chemistry as a proxy for the missing Ti chemistry.…”
Section: Updated Ti-chemistry In Cloudymentioning
confidence: 99%
“…For example, in the reference column Si5209 refers a copied reaction from Si reaction of UDfA2012 with the reaction number 5209. Ref 1, 2, and 3 refer to Churchwell et al (1980), Ramírez et al (2020), andTsai et al (2021), respectively. The rate coefficient for the reaction, Ti + + H − → Ti + H, is taken from Dalgarno & McCray (1973).…”
Section: Appendixmentioning
confidence: 99%
“…Hobbs et al (2019) used a photochemical kinetic model to show that the abundances of C-and O-bearing species, such as H 2 O and CO, are insensitive to N/H ratio in hot Jupiters like HD 209458b. Ramírez et al (2020) also investigated the impact of N/H ratio on TiO abundances in ultrahot Jupiters and found that the TiO abundance is nearly independent of N/H. Since the abundances of C-and O-bearing species are insensitive to bulk nitrogen abundance in substellar atmospheres, it appears that the only route to diagnose the bulk nitrogen abundance of a giant planet is from NH 3 and/or HCN.…”
Section: Introductionmentioning
confidence: 99%